CLINICAL MANIFESTATIONS OF TOPICAL CORTICOSTEROID WITHDRAWAL SYNDROME IN ATOPIC DERMATITIS - Saidova , Zilola; Abdurakhmanova , Zarifa; Tairova , Madina (WORLD INTERNATIONAL CONFERENCE ON SCIENCE, TECHNOLOGY AND EDUCATION, 2026)
This article reviews current understanding of topical corticosteroid withdrawal syndrome (TCWS) in atopic dermatitis. It highlights the rising prevalence of atopic dermatitis among both children and adults, as well as the impact of urbanization and environmental factors on its incidence. Particular attention is paid to the development of dependence on topical steroids, the “vicious cycle” mechanism, and the phenomenon of tachyphylaxis. The clinical differences between TSW and exacerbations of atopic dermatitis are analyzed, which is important for diagnosis and the selection of treatment strategies.